A study of information systems issues, practices, and leadership in Europe. Issue 1 (2nd January 2019) - Kappelman, Leon; Johnson, Vess; Torres, Russell; Maurer, Chris; McLean, Ephraim
ABSTRACT: In the summer of 2017, an online survey was administered to European IT executives, asking them about their concerns, spending, investments, cloud usage, security, workforce, reporting relationships, and other issues of importance. A total of 276 organisations responded. Their top-five most important IT management concerns were: Alignment, Digital Transformation, Cybersecurity, Cost, and Business Agility. Similarly, their top-five largest IT investments were: Analytics, Software Development, Cloud, Cybersecurity, and ERP. The average age of the CIOs was 49, 41% reported to their CEO, and nearly two-thirds interacted with their CEO at least weekly. Almost three-quarters came from previous IT positions, but only a 16% from IT within their current organisations. On average, CIOs spend about 20% of their time interacting with members of the C-suite, about 26% with their IT employees, and about 16% with other corporate employees. IT spending was up nearly 5% over the previous year and averaged almost 7% of corporate revenues. Over two-thirds of companies reported the number of IT employees and salaries were both up and spending on Cloud also increased.This paper explores these and other findings and their implications for IT management practice. Comparisons with US -based organisations are also included.